Inflammation and JNK's Role in Niacin-GPR109A Diminished Flushed Effect in Microglial and Neuronal Cells With Relevance to Schizophrenia - Ansarey, Sabrina H. (Frontiers in Psychiatry, 2021)
Schizophrenia is a neuropsychiatric illness, with no single definitive etiology, making it hard to treat. Antipsychotics are not fully effective as they treat psychosis, and not the cognitive or negative symptoms. Antipsychotics fail to alleviate symptoms, when patients enter their chronic stage of illness. Topical application of niacin showed diminished skin flush in majority of schizophrenia patients, compared to general population, who showed flushing. The niacin skin flush test is useful for identifying schizophrenia patients at their ultra-high risk stage, understanding this pathology may introduce an effective treatment. This standard literature review aims to understand the pathology behind diminished skin flush response, while linking it back to neuron and microglia. Firstly, it suggests that there are altered proteins in the GPR109A-COX-prostaglandin pathway, inflammatory imbalance, and kinase signalling pathway, c-Jun N-terminal kinase (JNK) which are associated with the diminished flush. Secondly, genes from GPR109A-COX-prostaglandin pathway were matched against 128-loci Genome Wide Association Study (GWAS) for schizophrenia using GeneCards, where it suggests that G-coupled receptor-109A (GPR109A) may have a genetic mutation, resulting in diminished flush. This review also suggests that there may be increased proinflammatory mediators in the GPR109A-COX-prostaglandin pathway, which contributes to the diminished flush pathology. Increased proinflammatory markers may induce microglial activated neuronal death. Lastly, this thesis explores c-Jun N-terminal kinase (JNK) role on proinflammatory mediators, proteins in GPR109A-COX-prostaglandin pathway, microglial activation and neuronal death, respectively. Inhibiting JNK, may reverse the changes observed in diminished flush response, which might make it a good therapeutical target.